If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+10-2x+5=60
We move all terms to the left:
5x+10-2x+5-(60)=0
We add all the numbers together, and all the variables
3x-45=0
We move all terms containing x to the left, all other terms to the right
3x=45
x=45/3
x=15
| X^4-3x-13=0 | | (5x-46)+(2x+5)=180 | | 3/2x+10=1/2x-10 | | 7a+3=a-5+-16 | | 5+p=5-p | | 5–8m=5m+5+2m | | -9×x=-117 | | 1/2(100+8x)=25-9x | | -2x+9=69 | | b/19-8b/19=14/19 | | 5f/3-2/3=3f | | 9x+2=3x+7 | | -50=-4x-6x=5 | | 3x+52+5x-22=180 | | (9/2)(x+3)=27 | | 7x+3x=10-7 | | 5y-y+1/3=6y+1/5 | | 12(2x-8)=4(5-2x)+3(7-3x1 | | |m|+2=11 | | 60=3/5x | | 0,3x-9=0 | | -5-(15y-1)=-2(7y-16)-y | | -52-7x=47+12x | | 7z/9+1=3z/6 | | -2(r+8)=-9 | | 16x=12*18 | | 4=3/4x+1 | | 1/4t+8=11 | | -7-8b=-9b | | (x+5)x35-462=1,463 | | -3(x+8)+3=11(1x-7) | | y-9=-8y |